Modern weapons top speed, armament, caliber, rate of fire - Dougherty, Martin J. (Compared and contrasted series, 2012)
Modern Weapons allows the reader to compare the key weapons of modern armies side by side. The book includes air, sea and land weapons, both vehicles and small arms, in a spread by spread format for ease of use packed with specially created charts, graphs, and artworks.